Early termination does not negatively impact the outcome of adjuvant immunotherapy in melanoma - Tomsitz, Dirk; Livingstone, Elisabeth; Loquai, Carmen; Kaatz, Martin; Leiter, Ulrike; Schilling, Bastian; Terheyden, Patrick; Hassel, Jessica C.; Sachse, Michael; Ulrich, Jens; Dippel, Edgar; Meiss, Frank; et al. (Journal of the European Academy of Dermatology and Venereology, 2025)
Background Adjuvant treatment with anti-PD1 antibodies has been shown to effectively reduce the risk of recurrence in patients with resected metastatic melanoma. Whether a full 12-month duration of treatment is needed to achieve full clinical benefit is not known. This study investigated the survival outcome depending on the duration of adjuvant anti-PD1 therapy. Methods From the prospective multicentre real-world skin cancer registry ADOREG data of 620 patients who finished adjuvant treatment with nivolumab or pembrolizumab for AJCCv8 stage III/IV resected melanoma was analyzed. Recurrence-free survival (RFS) and overall survival (OS) were compared between patients with regular treatment duration (52 ± 4 weeks; n = 229) and no disease recurrence during therapy (A1) and patients with a premature end of treatment (<48 weeks; n = 214, B). Patients with disease recurrence during adjuvant treatment were included in cohort A2. Results The median duration of follow-up was 26.0 months [interquartile range (IQR) 18.0-34.0] in group A1 [median treatment duration 51.3 weeks (IQR 50.0-52.1) and 19.0 months (IQR 13.0-29.0)] in group B [median treatment duration 22.2 weeks (IQR 10.0-34.8)]. Reasons for early discontinuation were treatment-related side effects in 45.3% (n = 97) and other reasons than toxicity in 54.7% (n = 117). The 2-year rate of RFS was 72.4% (95% CI, 68.5-76.3) for patients in group B and 51.5% (95% CI, 48.8-54.2) in patients with regular and intended regular treatment duration (A1 plus A2). When analysing the patients who did not relapse during adjuvant treatment (A1), there was a significantly higher RFS rate of 84.1% (95% CI, 81.5-86.7). When only assessing patients with a recurrence after more than 12 months after initiation of therapy, there was a trend towards better RFS in patients with regular treatment duration. Conclusion In patients with resected metastatic melanoma, shorter treatment duration with anti-PD1 antibodies is not associated with a worse outcome.
Zuerst veröffentlicht: 22. März 2025
Gesehen am 08.10.2025